Perawatan luka dengan metode moist wound healing dan salep terhadap integritas kulit dan jaringan pada luka diabetes melitus tipe 2: studi kasus pada wanita lanjut usia - Hikmawati, Hikmawati; Jayatri, Jayatri; Wijayati, Fitri (PT Karya Inovasi Berkelanjutan, 2024)
Type 2 diabetes mellitus is a chronic metabolic disease that carries a high risk of complications, including diabetic ulcers that compromise skin and tissue integrity. Appropriate wound management is essential to accelerate healing and prevent further infection. This case study aimed to evaluate the application of the moist wound healing method combined with Metcovazin ointment in improving skin and tissue integrity in a patient with a diabetic foot ulcer. The subject was a 52-year-old female diagnosed with type 2 diabetes mellitus and a diabetic ulcer, admitted to Baubau City General Hospital. The wound care intervention was conducted over four days, with treatments administered every two days. Observations revealed improvements in wound condition, as indicated by a reduction in wound length from 14 cm to 13.9 cm, a decrease in pain scale from 4 to 2, 80% granulation tissue formation, 20% epithelialization, and the absence of necrotic tissue. These findings suggest that the moist wound healing method combined with Metcovazin ointment supports optimal tissue regeneration by maintaining a moist wound environment. Nevertheless, this intervention should be integrated into a comprehensive therapeutic approach, including medical treatment and nutritional management, to achieve optimal outcomes.